Good Psychiatric Management and Dialectical Behavior Therapy A Clinician's Guide to Integration and Stepped Care. - Sonley, Anne K.I (American Psychiatric Association Publishing, 2020)
This manual, edited by experts on BPD, provides a framework for implementing a stepped care model in settings where access to specialized treatments is limited. The authors contend that the principles of good psychiatric management (GPM) represent a basic foundation that all clinicians can learn and that combined with dialectical behavior therapy (DBT), one of the most effective newer treatment modalities, progress can indeed be realized.